2013
DOI: 10.1051/mmnp/20138407
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Plant Growth Models: Methodology and Implementation in the PYGMALION platform

Abstract: Abstract. Mathematical models of plant growth are generally characterized by a large number of interacting processes, a large number of model parameters and costly experimental data acquisition. Such complexities make model parameterization a difficult process. Moreover, there is a large variety of models that coexist in the literature with generally an absence of benchmarking between the different approaches and insufficient model evaluation. In this context, this paper aims at enhancing good modelling practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Generally, our approach fits into a current general trend of development of modular models, with generic modules that can be shared by other modelers. This trend goes hand in hand with the increasing number of modeling platforms: Pygmalion in our case (Cournède et al, 2013), OpenAlea (Pradal et al, 2004), GroIMP (Kniemeyer et al, 2006) It is expected that mechanistic description of ecophysiological processes improves the model predictive capacities and their ability to differentiate between genotypes (Allen et al, 2005;Minchin and Lacointe, 2005;Bertheloot et al, 2011 (Christopoulos and Michael, 2000). Moreover, the parameterization effort of these more and more complex models should always be taken into account when improving their mechanistic description, to prevent from a high level of uncertainty in the parameters which may hinder the original purposes of the model in terms of prediction and genotypic differentiation.…”
Section: Model Application: An Exploratory Study On Specific Leaf Areamentioning
confidence: 93%
“…Generally, our approach fits into a current general trend of development of modular models, with generic modules that can be shared by other modelers. This trend goes hand in hand with the increasing number of modeling platforms: Pygmalion in our case (Cournède et al, 2013), OpenAlea (Pradal et al, 2004), GroIMP (Kniemeyer et al, 2006) It is expected that mechanistic description of ecophysiological processes improves the model predictive capacities and their ability to differentiate between genotypes (Allen et al, 2005;Minchin and Lacointe, 2005;Bertheloot et al, 2011 (Christopoulos and Michael, 2000). Moreover, the parameterization effort of these more and more complex models should always be taken into account when improving their mechanistic description, to prevent from a high level of uncertainty in the parameters which may hinder the original purposes of the model in terms of prediction and genotypic differentiation.…”
Section: Model Application: An Exploratory Study On Specific Leaf Areamentioning
confidence: 93%
“…Because no model was available in DSSAT for sugarbeet, Anar et al (2015) modified and incorporated CERES-Beet (Leviel, 2000) into DSSAT 4.6.1, and the resultant sugarbeet model is termed CSM-CERES-Beet. Baey et al (2014) showed that CERES-Beet provided overall good predictions of plant growth and yield for sugarbeets after comparing CERESBeet with four other sugarbeet models: GreenLab (Vos et al, 2007), LNAS (Cournede et al, 2013), STICS (Brisson et al, 1998), and Pilote (Taky, 2008).…”
Section: Rzwqm and Csm-ceres-beetmentioning
confidence: 99%
“…Mathematically speaking, if we consider the system of interest as the plant in its environment (or a population of plants, or a specific part of the plant for models at smaller scales) plant growth models could formally be represented in the very generic following form: Y=ffalse(θ,Efalse) where: Y represents all the phenotypic traits of interest, and is generally a real-valued function of space and time. f represents the functional equations (usually dynamical, see for example the description of plant growth models as dynamic state space models and hidden Markov models in Cournède et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…f represents the functional equations (usually dynamical, see for example the description of plant growth models as dynamic state space models and hidden Markov models in Cournède et al, 2013). …”
Section: Introductionmentioning
confidence: 99%